Association between depression and maintenance medication adherence among Medicare beneficiaries with chronic obstructive pulmonary disease. (19th April 2013) - Qian, Jingjing; Simoni‐Wastila, Linda; Rattinger, Gail B.; Zuckerman, Ilene H.; Lehmann, Susan; Wei, Yu‐Jung J.; Stuart, Bruce
<x xml:space="preserve">Abstract</x> Objective Depression is a significant comorbidity in patients with chronic obstructive pulmonary disease (COPD). Although comorbid depression is associated with low use and poor adherence to medications treating other chronic conditions, evidence of the relationship between depression and COPD management is limited. This study estimated the association between depression and COPD maintenance medication (MM) adherence among patients with COPD. Methods This cross‐sectional study used a 5% random sample of 2006–2007 Chronic Condition Warehouse data. Medicare beneficiaries enrolled in Parts A, B, and D plans with diagnosed COPD who survived through 2006 were included (n = 74, 863). COPD MM adherence was measured as medication discontinuation and proportion of days covered (PDC). Depression was identified through the International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes. Multivariable models with modified generalized estimating equations were used to estimate adjusted association between depression diagnosis and medication adherence, controlling for sociodemographics, comorbidities, and disease severity. Results Among the sample, about one third (33.6%) had diagnosed depression. More than half (61.8%) of beneficiaries with COPD filled at least one COPD MM prescription. Depressed beneficiaries had a higher likelihood of using COPD MM than non‐depressed beneficiaries (adjusted prevalence ratios [PR] = 1.02; 95% confidence intervals [CI] = 1.01, 1.03). Among COPD MM users, depressed beneficiaries were more likely to discontinue medications (PR = 1.09; 95% CI = 1.04, 1.14) and less likely to exhibit PDC ≥ 0.80 (PR = 0.89; 95% CI = 0.86, 0.92) than non‐depressed beneficiaries. Conclusions Depression is prevalent in Medicare beneficiaries with COPD and independently associated with lower COPD MM adherence. Interventions to improve medication adherence for COPD patients may consider management of comorbidities such as depression. Copyright © 2013 John Wiley & Sons, Ltd.